Pengaruh Mobilisasi Saraf Medianus Terhadap Tingkat Nyeri Pada Penderita Carpal Tunnel Syndrome di RS Bina Sehat Jember - Arum Mega Adhani; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro; Ahmad Abdullah (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Carpal Tunnel Syndrome is an upper extremity disorder caused by narrowing of the carpal tunnel. This study aims to analyze the level of pain in patients with Carpal Tunnel Syndrome before and after mobilization of the medianus nerve.Methods: The independent variable of this study was the mobilization of the medianus nerve, while the dependent variable was the level of pain. There were 14 respondents in this study using purposive sampling technique. The design of this study used a one group pretest and posttest design.Results: The results of this study are p-value = 0.002 (p <0.05) meaning that there is an influence of medianus nerve mobilization on the pain level of Carpal Tunnel Syndrome sufferers at Bina Sehat Hospital Jember in 2021Conclusion: 1. The average pain scale of patients with Carpal Tunnel Syndrome before mobilizing the median nerve was 4.86, which is moderate pain.2. The average pain scale of patients with Carpal Tunnel Syndrome after mobilizing the median nerve is 3, namely mild pain.3. There is an effect of median nerve mobilization on the pain level of Carpal Tunnel Syndrome sufferers at Bina Sehat Hospital Jember with p-value = 0.002 (p<0.05)